2001
DOI: 10.2460/javma.2001.218.884
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of morphine administered by constant-rate intravenous infusion or intermittent intramuscular injection in dogs

Abstract: Results indicated that administration of morphine as a constant-rate IV infusion at a dose of 0.12 mg/kg/h induced effects similar to those obtained with administration at a dose of 1 mg/kg, IM, every 4 hours in dogs undergoing laparotomy. Panting was attributed to an opioid-induced resetting of the hypothalamic temperature set point, rather than respiratory depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
80
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(92 citation statements)
references
References 10 publications
10
80
2
Order By: Relevance
“…Previous authors reported reduction in heart rate with use of morphine (LUCAS et al, 2001;WIESE;MARCH, 2003) and fentanyl (STEAGALL et al, 2006;BUFALARI et al, 2007;UEYAMA et al, 2009) CRIs. Steagall et al (2006) showed that hypertension spikes were avoided by fentanyl CRI administration in dogs, compared with a control group.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous authors reported reduction in heart rate with use of morphine (LUCAS et al, 2001;WIESE;MARCH, 2003) and fentanyl (STEAGALL et al, 2006;BUFALARI et al, 2007;UEYAMA et al, 2009) CRIs. Steagall et al (2006) showed that hypertension spikes were avoided by fentanyl CRI administration in dogs, compared with a control group.…”
Section: Discussionmentioning
confidence: 99%
“…The doses and drugs evaluated in the records are already indicated for use in CRI and were in accordance with low doses described in the literature. These protocols are known to reduce the isoflurane requirement without adversely affecting hemodynamics or obvious adverse effects (LUCAS et al, 2001;WIESE;MARCH, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It can contribute for minimizing hyperglycemia as well as the release of cortisol and catecholamines that happen in response to pain. This effect has been demonstrated in bitches premedicated with morphine and undergoing ovariohysterectomy or laparotomy (Lucas et al, 2001). The combination of morphine and local anesthetics through the epidural route can increase the duration of the block, as well as its analgesic efficacy.…”
Section: Introductionmentioning
confidence: 92%